2007
DOI: 10.1182/blood-2005-12-028019
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction between Kit and the interleukin-7 receptor

Abstract: In vivo analyses of thymopoiesis in mice defective in signaling through Kit and gammac or Kit and IL-7Ralpha demonstrate synergy and partial complementation of gammac or IL-7-mediated signaling by the Kit signaling pathway. Our molecular analysis in T-lymphoid cells as well as in nonhematopoietic cells shows that Kit and IL-7R signaling pathways directly interact. KL-mediated activation of Kit induced strong tyrosine phosphorylation of gammac and IL-7Ralpha in the absence of IL-7. Activated Kit formed a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
2
21
1
Order By: Relevance
“…Such mechanisms may potentially include yet unidentified, IL-7R␣ ligands or cross-activation of IL-7R␣ in Il7 Ϫ/Ϫ mice through other pathways, such as KIT, as recently suggested. 31 Although our findings do not support a key role of TSLP in IL-7-dependent or -independent steady state thymopoiesis, it remains possible that TSLP might be involved in T lymphopoiesis in conditions other than steady state.…”
Section: Discussioncontrasting
confidence: 49%
“…Such mechanisms may potentially include yet unidentified, IL-7R␣ ligands or cross-activation of IL-7R␣ in Il7 Ϫ/Ϫ mice through other pathways, such as KIT, as recently suggested. 31 Although our findings do not support a key role of TSLP in IL-7-dependent or -independent steady state thymopoiesis, it remains possible that TSLP might be involved in T lymphopoiesis in conditions other than steady state.…”
Section: Discussioncontrasting
confidence: 49%
“…It has been documented that c-Kit is able to crosstalk with many growth factor and cytokine receptors [26][27][28]81]. For example, erythropoietin and SCF have synergistic effects on erythropoiesis.…”
Section: C-kit and Insulin Receptor Crosstalk In Isletsmentioning
confidence: 99%
“…c-Kit signalling pathways are not simple linear reactions, but, rather, integrated inputs from different pathways that determine the biological consequences in different cellular contexts. For instance, c-Kit crosstalks with the erythropoietin receptor or interleukin receptors to recruit common downstream signalling molecules, creating a method for modulating diverse physiological responses [26][27][28][29].…”
Section: Scf and C-kit Signalling Pathwaysmentioning
confidence: 99%
“…In support of such a possibility, evidence has recently been provided for such transactivation as an explanation for the more severe lymphoid phenotype in IL-7 receptor-than IL-7 ligand-deficient mice. 27 Resolving the conflicting results with regard to a potential role of FLT3 receptor and ligand in regulation of mouse HSCs has considerable implications for normal and leukemic hematopoiesis in man. Several studies have suggested that FLT3 is expressed on candidate normal human HSCs, [28][29][30] and greater than 30% of acute myeloid leukemias (AMLs) have activating mutations in the FLT3 receptor.…”
Section: Introductionmentioning
confidence: 99%